(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article presents the foundations and concepts related to writing and theater practices conducted in public basic education schools in the state of Santa Catarina, called the ETC Workshop, designed and led by the author. The study revealed strategies that highlight writing as a means of inscription in the world, conceptualizing teaching as a dialogical action that emphasizes the presence of an active body in classrooms. It proposes playful games and words, aiming for participants to connect with their own writing through a whirlwind pedagogy, seeking to experiment with a writing process that engages the whole body through games and theatrical exercises in the school.